"I want to bring this light to those in despair" – the Tokyo 2020 torch relay and the creation of Olympic legacies. Issue 1 (2nd January 2023) - Niehaus, Andreas
ABSTRACT: Mega sport events like the Olympic Games leave their marks on hosting nations and often become important lieux de mémoire in the history of a nation. In this article, I will analyze the Tokyo 2020 torch relay as a highly ritualistic and highly choreographed act that creates a space of and for symbolic practices and performances, and I will use it as a case study to show how the torch relay contributes to the creation of an Olympic legacy in Japan. My argument is divided into four sections. In each section, I will focus on a different area of the "microcosm of the torch relay" to shed light on chosen official strategies and efforts of Japanese politics, the IOC, the JOC, and the Tokyo 2020 Organizing Committee to create a 2020 Olympics narrative and future legacies. At the same time, I will challenge these efforts, strategies, and practices in terms of underlying intentions, hidden agendas, their impact and (failed) success by examining some of the many obstacles, opposing voices, and counter-narratives along the way of the torch relay, as well as how the micro-narratives of individual torch bearers may be the most enduring memories of the Tokyo 2020 torch relay.